Gender component of self-assessment of physical development of schoolchildren aged 11-13 - Tetyana Krutsevych; Oksana Marchenko; Liudmyla Pohasii; Olga Kholodova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to study of the peculiarities of self-assessment of physical development of schoolchildren aged 11-13 in the gender dimension. Material and methods: a set of research methods was used to solve the set tasks: theoretical (analysis, comparison, generalization, systematization); psychological-diagnostic (EV Bochenkova's questionnaire "Self-description of physical development", S. Bem's test-questionnaire "Masculinity - femininity"); generally accepted methods of mathematical statistics with the calculation of arithmetic means. Results: considers the peculiarities of the perception of their physical development of boys and girls 11-13 years, their gender identity (femininity, masculinity, androgyny) and identifies the impact of gender identity of students on the level of their overall self-esteem of physical development. Conclusions: the results of self-assessment of physical development and physical fitness of students gave us the opportunity to analyze the interdependence of the general level of self-esteem of students and their individual gender characteristics. It was found that the overall self-esteem of boys is influenced by more indicators than that of girls. Inflated self-esteem of physical development is mainly boys - representatives of masculine and androgynous psychological types.